PEMIKIRAN POLITIK DAN PEMERINTAHAN IKHWANUL MUSLIMIN PASCA MUSIM SEMI ARAB - Syawaluddin Syawaluddin (Pascasarjana IAIN Sorong, 2018)
This paper seeks to uncover the political thought and governmental concept of the Egyptian president, Muhammad Mursy, who was democratically elected for the first time, after the “Arab Spring”. Mursi is a members of the Muslim Brotherhood (IM) who was regarded as a forbidden party or an illegal mass organi- zation in Egypt before. This research based on literature research that seeks to collect the data related to the political thought and governmental concept of Muhammad Mursi as a members of the Muslim Brotherhood party, whether from the Internet or books that discuss about the phenomenon. This research found a num- ber of discoveries conducted by Mursi such as; the opening of a border gate in Gaza for Palestinians to enter Egypt, The vice-president’s from women and non-Muslims, restrict military gains in politics, and the others controversial decision.